2014
DOI: 10.1111/1471-0528.12769
|View full text |Cite
|
Sign up to set email alerts
|

Change in smoking status during two consecutive pregnancies: a population‐based cohort study

Abstract: Objective To investigate changes in tobacco smoking in two consecutive pregnancies and factors associated with the change.Design Population-based cohort study.Setting New South Wales, Australia, 2000-10.Population A total of 183 385 women having first and second singleton pregnancies.Methods Descriptive and multivariable logistic regression analyses of perinatal data linked to hospital admission data.Main outcome measures Proportion of women smoking during their first pregnancy who quit by their second, and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
9
0
4
Order By: Relevance
“…We found similar a similar percentage of women smoked at the start of both of their first two pregnancies to those reported elsewhere [ 36 , 37 ]. Whilst the time between pregnancies, where a women is still in relatively intense contact with healthcare professionals, is the ideal time to focus on the health of the entire family, particularly for mothers with a previous history of SGA birth, this is obviously a missed opportunity.…”
Section: Discussionsupporting
confidence: 90%
“…We found similar a similar percentage of women smoked at the start of both of their first two pregnancies to those reported elsewhere [ 36 , 37 ]. Whilst the time between pregnancies, where a women is still in relatively intense contact with healthcare professionals, is the ideal time to focus on the health of the entire family, particularly for mothers with a previous history of SGA birth, this is obviously a missed opportunity.…”
Section: Discussionsupporting
confidence: 90%
“…While this may happen sometimes, some examples, arguable, show the veracity of this opinion, that is, not using medical prophylaxes or insecticide-treated bed nets means wanting malaria, not taking or collecting one's anti-HIV or antiepilepsy medication reliably is a craving for AIDS or convulsions, not taking folic acid before and during early pregnancy means desiring a child with spina bifida, travelling by SUV to fitness training indicates a desire for the polar ice caps to melt and not refraining from tobacco use is choosing cancer or a growth retarded baby. 36 …”
Section: Peripartum Sterilisation Is Much More Effective and Economicmentioning
confidence: 99%
“…In one study in New South Wales, Australia, of 22 761 women recorded as smokers during their first pregnancy, 33.5% quit by their second pregnancy 12 . This change appeared to be influenced by adverse events in the first pregnancy such as gestational hypertension, large‐for‐gestational‐age baby, and stillbirth 12 . Other studies have demonstrated similar proportions of women quitting between pregnancies ranging from 24.9% 13,14 to 42.0% 13,15 in different samples of women.…”
Section: Introductionmentioning
confidence: 99%
“…There are surprisingly limited data on how smoking status changes either within or between pregnancies. In one study in New South Wales, Australia, of 22 761 women recorded as smokers during their first pregnancy, 33.5% quit by their second pregnancy 12 . This change appeared to be influenced by adverse events in the first pregnancy such as gestational hypertension, large‐for‐gestational‐age baby, and stillbirth 12 .…”
Section: Introductionmentioning
confidence: 99%